2018
DOI: 10.1503/cmaj.180194
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Cardiovascular Harmonized National Guidelines Endeavour (C-CHANGE) guideline for the prevention and management of cardiovascular disease in primary care: 2018 update

Abstract: a complete update of the Canadian Association of Cardiovascular Prevention and Rehabilitation and Obesity Canada guidelines and the addition of guidelines on heart failure. In each C-CHANGE cycle, efforts are made to improve and harmonize guideline development with all partner organizations so that each guideline scores highly on the AGREE II (Appraisal of Guidelines for Research & Evaluation II) Instrument, which evaluates the process of guideline development and quality of reporting. 17 The full 2018 C-CHANG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 103 publications
1
47
0
3
Order By: Relevance
“…This review has highlighted that various metrics of quality carbohydrates exist, and will resonate differently for consumers depending on their food values and needs. Canada’s position on GI labelling contradicts Canadian expert opinions for the management of diabetes and cardiovascular disease risk since guidelines recommend low-GI dietary patterns [ 92 , 96 ]. A recent study demonstrated that Canadians would be receptive to GI labelling as a tool to destigmatize carbohydrates and assist with choosing healthy carbohydrate foods [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review has highlighted that various metrics of quality carbohydrates exist, and will resonate differently for consumers depending on their food values and needs. Canada’s position on GI labelling contradicts Canadian expert opinions for the management of diabetes and cardiovascular disease risk since guidelines recommend low-GI dietary patterns [ 92 , 96 ]. A recent study demonstrated that Canadians would be receptive to GI labelling as a tool to destigmatize carbohydrates and assist with choosing healthy carbohydrate foods [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for the management of diabetes in Canada, Australia, Europe, the UK, and the US acknowledge that low GI dietary patterns can be used to assist with blood glucose management [ 92 , 93 , 94 , 95 ]. In Canada, low glycemic index diets have also been acknowledged as a strategy for the prevention and management for cardiovascular disease [ 96 ].…”
Section: Labelling Foods For Carbohydrate Qualitymentioning
confidence: 99%
“…This analysis focused on a cohort of patients with hypertension, as guidelines recommend that tobacco use status should be updated on a regular basis for these patients [8]. Patients were identified as hypertensive if they met the validated definition developed by CPCSSN, which includes a combination of diagnostic codes related to hypertension and antihypertensive medications [9].…”
Section: Samplementioning
confidence: 99%
“…Finally, it is important to recommend that patients engage in a multifaceted approach to lower their cardiovascular risk, such as healthy eating, regular physical activity, smoking cessation, healthy weight goals, stress reduction and appropriate blood pressure and lipid control. 3 It is recommended that any patient with cardiovascular risk factors undergo an objective assessment of their cardiovascular risk (e.g., Framingham Risk Score), which can be discussed with the patient to help inform and motivate their approach to lowering their cardiovascular risk. 26…”
Section: Stepwise Approachmentioning
confidence: 99%
“…2 ASA is recommended in patients with established CVD (i.e., secondary prevention). 3 However, the role of ASA in those without CVD (i.e., primary prevention) is less clear. Previous meta-analyses have shown that ASA reduces the risk of cardiovascular events in patients without CVD but also increases the risk of major bleeding.…”
Section: Introductionmentioning
confidence: 99%